2009
DOI: 10.1177/0013164409344522
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Structure of Positive and Negative Affect: A Confirmatory Factor Analysis of the PANAS

Abstract: This study tested five confirmatory factor analytic (CFA) models of the Positive Affect Negative Affect Schedule (PANAS) to provide validity evidence based on its internal structure. A sample of 223 club sport athletes indicated their emotions during the past week. Results revealed that an orthogonal two-factor CFA model, specifying error correlations according to Zevon and Tellegen’s mood content categories, provided the best fit to our data. In addition, parameter estimates for this model suggest that PANAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
93
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 26 publications
14
93
0
11
Order By: Relevance
“…Table 1 shows the goodness--of-fi t indices of the models tested. Zevon and Tellegens's (1982) content categories (Crawford & Henry, 2004;Tuccitto et al, 2010) and the cross-loading of excited between PA and NA (Mackinnon et al, 1999) We started our analysis by testing the two-factor independent model originally proposed by Watson et al (1988). We specifi ed a measurement model predicting that the 20 items of the full version loaded on two uncorrelated latent variables PA and NA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows the goodness--of-fi t indices of the models tested. Zevon and Tellegens's (1982) content categories (Crawford & Henry, 2004;Tuccitto et al, 2010) and the cross-loading of excited between PA and NA (Mackinnon et al, 1999) We started our analysis by testing the two-factor independent model originally proposed by Watson et al (1988). We specifi ed a measurement model predicting that the 20 items of the full version loaded on two uncorrelated latent variables PA and NA.…”
Section: Resultsmentioning
confidence: 99%
“…The two-factor model was also the best fi tting model in the study of Terracciano et al (2003), where PA and NA scales remained substantially independent after accounting for measurement error. In the studies of Crawford and Henry (2004) and Tuccitto, Giacobbi and Leite (2010), the best fi tting model was also a two-factor model, specifying correlations according to the mood content categories of Zevon and Tellegen (1982). However, while the relationship between PA and NA was independent in the study of Tuccitto et al (2010) it was not completely independent in the study of Crawford and Henry (2004).…”
Section: Factorial Structure Of the Panasmentioning
confidence: 99%
See 1 more Smart Citation
“…We make use of both techniques here. strongly negatively correlated-so that individuals can be experiencing both positive and negative affect simultaneously (Watson et al 1988;Tuccitto et al 2010). ONS-happy (''Overall, how happy did you feel yesterday?'')…”
Section: The Relation Between Evaluative and Experienced Well-being Mmentioning
confidence: 99%
“…Factor analyses have confirmed that the scale measures two primarily independent constructs (Tuccitto, Giacobbi, & Leite, 2009). For state affect ratings, the positive affect scale possesses a test-retest reliability of r = .54, while the negative affect scale possesses a test-retest reliability of r = .45 (Watson et aI., 1988).…”
Section: Outcome Variable Measuresmentioning
confidence: 81%